Factors Associated with Mortality in COVID-19 Patients: A Systematic Review and Meta-Analysis - Mojtaba SEPANDI; Maryam TAGHDIR; Yousef ALIMOHAMADI; Sima AFRASHTEH; Hadiseh HOSAMIRUDSARI (Tehran University of Medical Sciences, 2020)
Background: The current study aimed to identify effective factors on the death among COVID-19 patients. Methods: All articles published in the period Jan 1, 2020, to Mar 23, 2020, written in English and reporting factors associated with COVID-19 mortality were reviewed. The random-effects model with 95% CI was used to calculate the pooled Odds Ratio (OR) and Hazard Ratio (HR). Data were analyzed using Stata ver.11.0. Results: The older age OR: 1.21(1.10-1.33) and male gender OR: 1.41(1.04-1.89) were most prone to death due to COVID-19. The Comorbidity with some chronic diseases such as Diabetes type2 OR: 2.42(1.06-5.52), Hypertension OR: 2.54(1.21-5.32), Kidney disorder OR: 2.61(1.22-5.60), Respiratory disorder 3.09 (1.39-6.88) and Heart diseases OR: 4.37 (1.13-16.90) can increase the risk of COVID19 mortality. Conclusion: Infection with COVID-19 is associated with substantial mortality mainly in older patients with comorbidities. We found the significant effect of age, gender and comorbidities such as Diabetes Mellitus, Hypertension, Kidney disorders and Heart diseases on the risk of death in patients with COVID-19. The factors associated with mortality found in this research can help to recognize patients with COVID-19 who are at higher risk of a poor prognosis. Monitoring these factors can serve to give early warning for the appropriate interventions.